2014
DOI: 10.4103/2249-4863.130269
|View full text |Cite
|
Sign up to set email alerts
|

Role of health education and self-action plan in improving the drug compliance in bronchial asthma

Abstract: Background:Considering the prevalence and associated burden of disease due to bronchial asthma, it is mandatory to obtain an optimal control of the disease and to improve outcomes for these patients. But it has been observed that there is very poor adherence to the inhalational therapy which leads to the suboptimal control of the disease.Objectives of the Study:To study the adherence for aerosol therapy in bronchial asthma patients and to assess the impact of health education and self-action plan in improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…It clearly shows that a better understanding of attitudes towards asthma medication should be helpful in encouraging good patient adherence to treatment. 9 It was found that the attitudes of peers towards asthma patients were clearly different from those of the other members in the family. This will lead to anxiety and depression among asthma patients and thus, affecting the compliance to the medications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It clearly shows that a better understanding of attitudes towards asthma medication should be helpful in encouraging good patient adherence to treatment. 9 It was found that the attitudes of peers towards asthma patients were clearly different from those of the other members in the family. This will lead to anxiety and depression among asthma patients and thus, affecting the compliance to the medications.…”
Section: Discussionmentioning
confidence: 99%
“…Educational methods tailored to needs of each patient and effective behavior towards disease and its management is very essential. In one of our study 9 it was shown that with various tools of education, the compliance in medications could be increased by almost another 40%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other concerns voiced by the parents were the cost of inhaled medication and difficulty in using inhalers. 26 Recently, Gaude et al 27 has observed that the compliance in bronchial asthma patients was just about 38.6%, and even after health education it improved by another 40%. Hence it is not only the responsibility of the parents, but also the treating physicians should be responsible for proper education regarding the inhalational therapy in bronchial asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Through this, understanding of various strategies must be tailored and individualised to have a meaningful impact on medication adherence. Such a recommendation has been seen within the medication adherence literature in hypertension [22], asthma [23] and depression [24]. However, this understanding is particularly valid in the osteoarthritis population given the acknowledged variability in health beliefs regarding the condition itself, irrespective of beliefs surrounding pharmacological management [25].…”
Section: Discussionmentioning
confidence: 94%